PENSION PROVISION FOR MILITARY PERSONNEL: INTERNATIONAL EXPERIENCE AND PROSPECTS FOR UKRAINE - Olena Sokurenko; Oksana Chervviakova; Iryna Bihunets (Baltic Journal of Economic Studies)
The provision of social protection for military personnel is a matter of significant priority within the scope of state policy. Military personnel are exposed to considerable risk in their daily efforts to defend the independence and territorial integrity of the nation. This issue is of particular pertinence to Ukraine, which is currently engaged in armed conflict with Russia. The purpose of this article is to review and analyse the pension provision experience for military personnel in some of the world's leading countries, including the United States of America, Great Britain, Germany, Israel, Sweden and Norway. Methodology. The following research methods are employed: dialectical, historical and legal, formal and logical, hermeneutics, generalization, comparison. Results. The objective of the study is to ascertain the merits of each model, in addition to the challenges and opportunities for adapting positive experiences to the prevailing conditions in Ukraine. The article provides a comprehensive analysis of the mixed pension system of the US, which integrates traditional long-service payments with accumulative components. It also examines the integrated model of Germany, which ensures equality between military and civilian employees through a unified social insurance system. The Israeli model is of particular interest, as it emphasises short-term but intensive service, accompanied by expanded social guarantees for veterans. The pension systems of the Scandinavian countries (Sweden and Norway) are also the subject of study, due to the transparent financing mechanisms, sustainability and efficient use of social resources that characterise them. Practical implications. Based on the research results, it is advisable for Ukraine to implement a mixed pension model that includes accumulative funds with state contributions, similar to the TSP system in the USA. This would reduce the budgetary burden while simultaneously encouraging the military to play an active role in building their own pension capital. Additionally, retraining programmes should be created to help veterans acquire new professional skills and integrate into the civilian sector. Value / Originality. Utilising the insights garnered from this experience, comprehensive recommendations for enhancing the Ukrainian pension system for servicemen are proposed.